A decolonial analysis of religious medicalisation of same-sex practices in South African Pentecostalism - Shingange, Themba; Mavhandu-Mudzusi, Azwihangwisi H. (Hervormde teologiese studies, 2024)
Same-sex practices are commonly medicalised in various global spaces. Some societies view same-sex practices as some form of disease that needs to be cured. In Africa, the influence of Christianity has prompted many communities to conclude that there are spiritual forces behind same-sex orientations and practices. Therefore, same-sex practices are demonised, and those identifying with these sexualities and gender identities are viewed as sick, or as having some form of mental illness. As a fast-growing and influential movement in South Africa, Christianity plays a critical role in this narrative. Against this backdrop, this article examined how some Pentecostal pastors in South Africa use God-talk to propel the narrative that medicalises same-sex practices and how these pastors claim to have miraculous powers to heal these practices. Consequently, the gender and sexuality commonly accepted within African religiosity and spirituality are pushed to the peripheries. Therefore, it is argued in this article that the colonial-missionary discourses regarding African sexualities and genders are at play within the religious medicalisation of same-sex narratives. Thus, there is a need to problematise and transform this narrative. This act can contribute to delinking African genders and sexualities from Western repressions and subjugation agendas. The discussion moved from the premise of decoloniality while adopting a multidisciplinary approach that incorporated theology, gender and sexuality studies, psychology, health, and socio-political sciences. Again, the article used secondary literature analysis to examine this phenomenon and to gain a thorough understanding of how African Pentecostalism continues to use God-talk to medicalise same-sex practices in contemporary South Africa and the repercussions thereof.ContributionThe study contributed to the existing knowledge that addresses religious challenges faced by people identifying with non-normative sexualities and genders in Africa. This can contribute to the transformation of religious medicalisation of same-sex practices in South Africa, and elsewhere.